Optimization Utilization Study Storage of Raknamo Dam Amabi Oefeto District Kupang Region - Bale, Frits Jeferson; Bisri, Muhammad; Wahyuni, Sri (Fakultas Teknik, Universitas Brawijaya, 2023)
Raknamo Irrigation area (1323 ha) has problems with water availability, especially during the dry season, which causes a decrease in the productivity of the agricultural products from local communities. This is due to the suboptimal water distribution system in the Raknamo Reservoir. This study aims to analyze and optimize water distribution in the Raknamo Reservoir to obtain the most optimal water distribution to fulfill agricultural land's water needs in various seasons. Optimization analysis is carried out using a deterministic dynamic program. With this program, a complex and large-scale problem can be dispart into several small parts (decomposition), which are then optimized. Based on the analysis results, the maximum profit that can be obtained from the cropping intensity is 16% in the normal season. Meanwhile, the highest increase of the land area is 218.64 ha. It is worth noting that this study uses a deterministic dynamic program for optimization analysis to dispose of the complex problem into smaller, manageable parts. This approach facilitates a more systematic and comprehensive analysis and provides a framework for future decision-making processes related to water management and agricultural planning. The study's methodology and findings can serve as a valuable reference for similar water-related challenges in other irrigation areas, thereby contributing to the broader agricultural research and sustainable water resource management field.